Agricultural Change and Development in WolaittaEthiopia, From 1960 –1970s - Yonas Alambo, Henok; Kummar Tripathy, Sishir (International Journal of Psychosocial Rehabilitation, 2020)
The Imperial government gave attention to agricultural transformation of the countryside since 1960s onwards by providing selected seed, extension services, fertilizers, market access, credit institutions and other modern agricultural inputs to achieve improvement in the agricultural output and yields in Ethiopia. As a result, Wolaitta experienced both large scale mechanized and small scale peasant agricultural changes. Therefore, the main purpose of this paper is to examine the development, success, challenge of mechanization of Bilate private farm, Bilate Tobacco state farm, Abaya agricultural enterprise and the development of Wolaitta Agricultural Development Unit (WADU) in Wolaitta Awrajja from 1960 to the end of 1970s. Then in 1975 the Bilate and Abaya private enterprises were nationalized and became state-owned farms, and WADU sustained its implementation under the new regime. The same thing happened for the previously Bilate state tobacco farm continued as it was. The people of Wolaitta benefited large from mechanization, commercialization and provision of agricultural inputs, farm implements, marketing cooperatives, and settlement schemes. As a result, infrastructures developed, cash crop yields increased, the landless peasants became change agents and price of agricultural output increased as well. In general, this study applied qualitative methodology and utilized both primary and secondary data by combining with oral data. Finally, this experience would be taken from Wolaitta mechanization and integrated package peasant agriculture for today and future development.